Lytic Lesions of Vertebrae Without Involvement of Intervertebral Disc- An Atypical Presentation of Spinal Tuberculosis (Bangladesh Journal of Medicine, 2016)
Tuberculosis is very common in our country. It can involve many organs and have broad spectrum of image presentation. It may resemble malignant diseases, especially in the elderly and thus confuse the judgement of the clinician. We report a case of a 58 year old gentleman presenting with chronic cough, low grade fever, weight loss for 16 months; features of progressive marrow failure for 8 months and severe low back pain without any neurological features for 2 months. The CT scan of spine revealed lytic lesions of vertebrae sparing the intervertebral discs, thus resembling metastatic lesions of bone. We approached this case as malignant disease initially, but found it to be a disseminated tuberculosis infection involving lungs, bone marrow and spine after a series of investigations. Though disseminated TB is not uncommon in our country, the purpose of presenting this case is to give emphasis that, clinicians should consider Potts disease (spinal tuberculosis) in the differential diagnosis of patients with back pain and destructive vertebral lesions. Proper diagnosis and anti-tuberculous treatment with or without surgery will result in cure of the patientBangladesh J Medicine Jul 2016; 27(2) : 81-85